REMEDIASI MISKONSEPSI MENGGUNAKAN MODEL FLIPPED CLASSROOM MATERI IMPULS DAN MOMENTUM DI SMA - Hikmatunnisa, Diah; Sahala S, Stepanus; Mahmudah, Diah (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis research aimed to remediate student?s misconceptions used Flipped Classroom model on Impulse and Momentum subject in Senior High School 7 Pontianak. This research used experiment method with pre-experimental design form and used Nonequivalent Control Group design. This sample used Nonprobability sampling technique, in which the outcome was class of XMIA 4 and XMIA 5 with total 64 students. The instrument of this research was a diagnostic test consist of 12 multiple choice questions with open reasoning. Based on the data analysis, the average percentage of student's misconception decreased from 86% to 30.5% after implemented Flipped Classroom model. The Two Proportion statistic test result with Zformula > Ztable (4.00 > 1.96) this result showed there was a significant difference between the two class. It showed that Flipped Classroom be able to decreased student?s misconception. The researcher hopes this model will be used as an alternative teaching physics remediation to student's misconceptions. Keywords: Flipped Classroom, Impulse and Momentum, Misconceptions,  Remediation,